Bcl-2 inhibitor resistance in diffuse large b-cell lymphoma: establishing a prognostic signature and targeting alpha protein kinase 1 - Ma, Jingjing; Wang, Yifan; Liu, Hong; Deng, Yuan; Shi, Yuye; Wei, Lulu; Chen, Qiuni; Wang, Chunling; Yu, Liang (Frontiers in Oncology, 2026)
BackgroundDrug resistance in diffuse large B-cell lymphoma (DLBCL) contributes to poor prognosis in 30–40% of newly diagnosed patients in the era of first-line rituximab combined with cyclophosphamide, doxorubicin, vincristine, and prednisone therapy. Targeting Bcl-2 has been shown to target for improve the prognosis of these patients, based on the clinical trials of its inhibitor, venetoclax. However, venetoclax resistance in DLBCL remains a challenge. Methods: The ‘WGCNA’ package was used to comprehensively screen for Bcl-2 inhibitor-resistant genes (Bcl-2RGs) and the Bcl-2RGs signature was established using LASSO regression analysis with ten-fold cross-validation. Results: The Bcl-2 signature is an effective prognostic prediction model using Gene Expression Omnibus data analysis. In addition, we demonstrated that the inhibition of alpha protein kinase 1 (ALPK1) decreased the proliferation of DLBCL cells and increased apoptosis. ALPK1 inhibitor treatment synergized with venetoclax to suppress the ALPK1/NFκB signaling pathway. Conclusion: Overall, we showed that the Bcl-2 signature could predict the prognosis of patients with DLBCL, and that ALPK1 could be a promising target for sensitizing patients with DLBCL to venetoclax therapy.MethodsThe ‘WGCNA’ package was used to comprehensively screen for Bcl-2 inhibitor-resistant genes (Bcl-2RGs) and the Bcl-2RGs signature was established using LASSO regression analysis with ten-fold cross-validation. Results: The Bcl-2 signature is an effective prognostic prediction model using Gene Expression Omnibus data analysis. In addition, we demonstrated that the inhibition of alpha protein kinase 1 (ALPK1) decreased the proliferation of DLBCL cells and increased apoptosis. ALPK1 inhibitor treatment synergized with venetoclax to suppress the ALPK1/NFκB signaling pathway. Conclusion: Overall, we showed that the Bcl-2 signature could predict the prognosis of patients with DLBCL, and that ALPK1 could be a promising target for sensitizing patients with DLBCL to venetoclax therapy.ResultsThe Bcl-2 signature is an effective prognostic prediction model using Gene Expression Omnibus data analysis. In addition, we demonstrated that the inhibition of alpha protein kinase 1 (ALPK1) decreased the proliferation of DLBCL cells and increased apoptosis. ALPK1 inhibitor treatment synergized with venetoclax to suppress the ALPK1/NFκB signaling pathway. Conclusion: Overall, we showed that the Bcl-2 signature could predict the prognosis of patients with DLBCL, and that ALPK1 could be a promising target for sensitizing patients with DLBCL to venetoclax therapy.ConclusionOverall, we showed that the Bcl-2 signature could predict the prognosis of patients with DLBCL, and that ALPK1 could be a promising target for sensitizing patients with DLBCL to venetoclax therapy.